Massive black hole binaries in LISA: multimessenger prospects and electromagnetic counterparts - Mangiagli, Alberto; Caprini, Chiara; Volonteri, Marta; Marsat, Sylvain; Vergani, Susanna; Tamanini, Nicola; Inchauspé, Henri (Physical review, 2022)
In the next decade, the Laser Interferometer Space Antenna (LISA) will detect the coalescence of massive black hole binaries (MBHBs) in the range [104,108] M⊙, up to z∼10. Their gravitational wave (GW) signal is expected to be accompanied by an electromagnetic counterpart (EMcp), generated by the gas accreting on the binary or on the remnant BH. In this work, we present the number and characteristics (such as redshift and mass distribution, apparent magnitudes or fluxes) of EMcps detectable jointly by LISA and some representative EM telescopes. We combine state-of-the-art astrophysical models for the galaxies formation and evolution to build the MBHBs catalogs, with Bayesian tools to estimate the binary sky position uncertainty from the GW signal. Exploiting additional information from the astrophysical models, such as the amount of accreted gas and the BH spins, we evaluate the expected EM emission in the soft x-ray, optical and radio bands. Overall, we predict between 7 and 20 EMcps in 4 yrs of joint observations by LISA and the considered EM facilities, depending on the astrophysical model. We also explore the impact of the hydrogen and dust obscuration of the optical and x-ray emissions, as well as of the collimation of the radio emission: these effects reduce the number to EMcps to 2 or 3, depending on the astrophysical model, again in 4 yrs of observations. Most of the EMcps are characterized by faint EM emission, challenging the observational capabilities of future telescopes. Finally, we also find that systems with multimodal sky position posterior distributions represent only a minority of cases and do not affect significantly the number of EMcps.
Gesehen am 31.01.2023